Tissue-specific role of RHBDF2 in cutaneous wound healing and hyperproliferative skin disease - Hosur, Vishnu (BMC Res Notes, 2017)
OBJECTIVE: Gain-of-function (GOF) mutations in RHBDF2 cause tylosis. Patients present with hyperproliferative skin, and keratinocytes from tylosis patients’ skin show an enhanced wound-healing phenotype. The curly bare mouse model of tylosis, carrying a GOF mutation in the Rhbdf2 gene (Rhbdf2 (cub)), presents with epidermal hyperplasia and shows accelerated cutaneous wound-healing phenotype through enhanced secretion of the epidermal growth factor receptor family ligand amphiregulin. Despite these advances in our understanding of tylosis, key questions remain. For instance, it is not known whether the disease is skin-specific, whether the immune system or the surrounding microenvironment plays a role, and whether mouse genetic background influences the hyperproliferative-skin and wound-healing phenotypes observed in Rhbdf2 (cub) mice. RESULTS: We performed bone marrow transfers and reciprocal skin transplants and found that bone marrow transfer from C57BL/6 (B6)-Rhbdf2 (cub/cub) donor mice to B6 wildtype recipient mice failed to transfer the hyperproliferative-skin and wound-healing phenotypes in B6 mice. Furthermore, skin grafts from B6 mice to the dorsal skin of B6-Rhbdf2 (cub/cub) mice maintained the phenotype of the donor mice. To test the influence of mouse genetic background, we backcrossed Rhbdf2 (cub) onto the MRL/MpJ strain and found that the hyperproliferative-skin and wound-healing phenotypes caused by the Rhbdf2 (cub) mutation persisted on the MRL/MpJ strain.